Parental discourse strategies in Indonesian multilingual families - Nia Pujiawati; Yasir Riady (Mitra Palupi, 2022)
Background: In Indonesia, the amount of family speaking more than one language recently increase in intensity. They not only speak their official language and mother tongue for daily communication, but do they also be fluent in another foreign language for example English. Purpose: The present study closely examines spontaneous interactions between parents and children and explore the family members’ efforts to shape children’s foreign language use and learning outcomes. The focus is on the parental discourse strategies which presents a sequential analysis of the child’s language mixing in interaction which each parent and how the parent reacts to that mixing. Design and methods: To obtain the data, open-ended questionnaires were sent out to five families in which the children actively use English in their daily conversation. Using Lanza’s (1997) parental discourse strategies. Results: the result reveals that parents mostly follow code-switching in negotiating and enforcing their children to maintain their communication in English.